2021
DOI: 10.3390/su13179863
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on Diverse Farm Systems in Tanzania and South Africa

Abstract: Emerging information on the interactions between the COVID-19 pandemic and global food systems have highlighted how the pandemic is accentuating food crises across Africa. Less clear, however, are how the impacts differ between farming systems. Drawing on 50 key informant interviews with farmers, village leaders and extension officers in South Africa and Tanzania, we identify the effects of COVID-19 and associated measures to curb the spread of the disease on farming production systems, the coping mechanisms a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 53 publications
(63 reference statements)
3
23
0
Order By: Relevance
“…A study by Rosenberg et al [58] on the impact of the COVID-19 pandemic on labour markets and economies of 16 southern African countries found that the COVID-19 pandemic was associated with increased job loss risk specifically in Angola, South Africa and Zimbabwe. These studies suggested the need to provide social and economic support to the most vulnerable groups [59][60][61] as well as the need to rethink future actions towards global food security, since COVID-19 greatly affected all its four pillars [56,59]. Furthermore, FI in urban areas is largely an outcome of income poverty often accompanied by lack of secure employment, but also includes living conditions and inconsistent access to water, sanitation, electricity and other resources that shape households' food utilization capacity [62].…”
Section: Prevalence Of Food Insecuritymentioning
confidence: 99%
“…A study by Rosenberg et al [58] on the impact of the COVID-19 pandemic on labour markets and economies of 16 southern African countries found that the COVID-19 pandemic was associated with increased job loss risk specifically in Angola, South Africa and Zimbabwe. These studies suggested the need to provide social and economic support to the most vulnerable groups [59][60][61] as well as the need to rethink future actions towards global food security, since COVID-19 greatly affected all its four pillars [56,59]. Furthermore, FI in urban areas is largely an outcome of income poverty often accompanied by lack of secure employment, but also includes living conditions and inconsistent access to water, sanitation, electricity and other resources that shape households' food utilization capacity [62].…”
Section: Prevalence Of Food Insecuritymentioning
confidence: 99%
“…They are wellpositioned to ensure continuity in food supplies amidst complex logistical and transport issues ( Haga, 2020 ; Lopez-Ridaura et al, 2021 ). The use of family labor by smallholder farms may enable them to overcome possible labor shortages in the context of supply chain disruptions with regard to harvesting, getting food to market, and other farm-related activities ( Haga, 2020 ; Tripathi et al, 2021 ). Based on the resilience theory, where diversity is a key socio-ecological determinant of resilience ( Walker and Salt, 2012 ), the food systems of smallholder farmers may have more diverse types of food environments.…”
Section: Introductionmentioning
confidence: 99%
“…The mitigation measures have resulted in market closures in India ( Kumar et al, 2021 ), low demand for farm produce in Bangladesh ( Hossain, 2020 ), shortages in agricultural inputs in many countries ( WHO, 2020 ), and labor availability problems for farming activities in Nepal ( Adhikari et al, 2021 ). As a consequence, farmers' incomes and purchasing power have been reduced, leaving farm households financially vulnerable ( Tripathi et al, 2021 ). Studies in India and Bangladesh show that farmers who produce perishable products, such as vegetables, were severely impacted by COVID-19 because of the loss of conventional markets and farmers having little option but to distroy unsold produce ( Adhikari et al, 2021 ; Alam and Khatun, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in India and Bangladesh show that farmers who produce perishable products, such as vegetables, were severely impacted by COVID-19 because of the loss of conventional markets and farmers having little option but to distroy unsold produce ( Adhikari et al, 2021 ; Alam and Khatun, 2021 ). Impacts such as this have badly affected small scale farmers' incomes and long-term financial security in Tanzania and South Africa ( Tripathi et al, 2021 ). Small scale farmers in many developing countries are struggling to remain financially viable and many are now living in poverty ( Workie et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%